2021
DOI: 10.1039/d1qm00240f
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state integrated micro-supercapacitor array construction with low-cost porous biochar

Abstract: The scalable production of flexible integrated micro-supercapacitors (MSCs) with high performance and low cost is urgently required. Printing is a promising strategy to build MSCs with designable shapes. Here, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The results showed that prints with a reflective optical density of more than 1.0 were obtained with excellent tonal reproduction ( Figure 4 b). Yuan et al [ 107 ] also developed a stabilized biochar-based ink made from fruit peels that can be integrated on different flexible substrates by SPE or program-controlled writing methods. This suggests that replacing fossil fuel charcoal with biochar for printing materials is a promising avenue, but more research is still needed to lay the theoretical foundation.…”
Section: Application Of Biochar In the Printing Fieldmentioning
confidence: 99%
“…The results showed that prints with a reflective optical density of more than 1.0 were obtained with excellent tonal reproduction ( Figure 4 b). Yuan et al [ 107 ] also developed a stabilized biochar-based ink made from fruit peels that can be integrated on different flexible substrates by SPE or program-controlled writing methods. This suggests that replacing fossil fuel charcoal with biochar for printing materials is a promising avenue, but more research is still needed to lay the theoretical foundation.…”
Section: Application Of Biochar In the Printing Fieldmentioning
confidence: 99%
“…A screen printing method was also applied to make solid-state flexible micro-supercapacitors with 3D boron carbon nitride microspheres (made via hydrothermal and annealing techniques), with an areal capacitance of 41.6 mF/cm 2 [195]. A simple fabrication process with screen printing was also employed to make solid-state integrated micro-supercapacitor arrays with porous activated biochar (Figure 13), which exhibited an areal capacitance of 116 mF/cm 2 and a high areal energy density of 9.3 µWh/cm 2 [196].…”
Section: Screen Printingmentioning
confidence: 99%